Emergence of Polyfunctional Cytotoxic CD4+ T Cells in Mycobacterium avium Immune Reconstitution Inflammatory Syndrome in Human Immunodeficiency Virus-Infected Patients. (10th March 2018) - Hsu, Denise C; Breglio, Kimberly F; Pei, Luxin; Wong, Chun-Shu; Andrade, Bruno B; Sheikh, Virginia; Smelkinson, Margery; Petrovas, Constantinos; Rupert, Adam; Gil-Santana, Leonardo; Zelazny, Adrian; Holland, Steven M; et al.
Abstract : The pathogenesis of IRIS has not been clearly elucidated. CD4 + T cells with exuberant cytokine production, polyfunctionality, cytotoxic potential, and low expression of T-bet, in concert with restoration of monocyte immune responses, may overwhelm available regulatory and inhibitory mechanisms, leading to IRIS. Abstract: Background: Immune reconstitution inflammatory syndrome (IRIS) is an aberrant inflammatory response in individuals with advanced human immunodeficiency virus (HIV) infection, after antiretroviral therapy (ART) initiation. The pathogenesis of Mycobacterium avium complex (MAC)–associated IRIS has not been fully elucidated. Methods: We investigated monocyte and CD4 + T-cell responses in vitro, tumor necrosis factor (TNF) expression in tissues, and plasma cytokines and inflammatory markers, in 13 HIV-infected patients with MAC-IRIS and 14 HIV-uninfected patients with pulmonary MAC infection. Results: Prior to ART, HIV-infected compared with HIV-uninfected patients, had reduced TNF + monocytes ( P = .013), although similar cytokine (interferon gamma [IFN-γ], TNF, interleukin 2 [IL-2], and interleukin 17 [IL-17])–expressing CD4 + T cells. During IRIS, monocyte cytokine production was restored. IFN-γ + ( P = .027), TNF + ( P = .004), and polyfunctional CD4 + T cells ( P = 0.03) also increased. These effectors were T-bet low, and some expressed markers of degranulation and cytotoxic potential. Blockade of cytotoxic T-lymphocyte associated protein 4 and lymphocyte activation gene-3 further increased CD4 + T-cell cytokine production. Tissue immunofluorescence showed higher proportions of CD4 + and CD68 + (monocyte/macrophage) cells expressed TNF during IRIS compared with HIV-uninfected patients. Plasma IFN-γ ( P = .048), C-reactive protein ( P = .008), and myeloperoxidase ( P < .001) levels also increased, whereas interleukin 10 decreased ( P = .008) during IRIS. Conclusions: Advanced HIV infection was associated with impaired MAC responses. Restoration of monocyte responses and expansion of polyfunctional MAC-specific T-bet low CD4 + T cells with cytotoxic potential after ART initiation may overwhelm existing regulatory and inhibitory mechanisms, leading to MAC-IRIS.